Monstrous flavors - Lancioni, Tarcisio (E|C, 2020)
In this paper we will not talk about food, but about taste in the sense to which aesthetics have accustomed us, of judgment based on aesthetic qualities. The monstrosity mentioned in the title, therefore, is not connected to food choices that could be judged "reprehensible", from the point of view of a food moral, but concerns the diffusion and appreciation of certain "aberrant" morphologies such as those of monsters.